MODELING OF OPTIMAL PROGRAM OF PRODUCTION AND SALES - V. M. Machulin; V. E. Sidorchuk (Литьë и металлургия, 2011)
Optimization of production program and binding of expenses to the real situation is one of the ways to change the strategy of the enterprise development.